Numerical Study of a Southwest Vortex Rainstorm Process Influenced by the Eastward Movement of Tibetan Plateau Vortex. (3rd May 2018) - Liu, Xiaoli; Ma, Endian; Cao, Zhibin; Jin, Shuanglong
Abstract : A number of studies revealed the possible eastward movement of the Tibetan Plateau low-pressure system in summer and indicated the enhancement effect of this process on the southwest vortex in the Sichuan Basin, which can induce strong convective precipitation and flood events in China. In this study, a numerical simulation of a southwest vortex rainstorm process was performed. The results show that the low-pressure system originated from the Tibetan Plateau affects the southwest vortex mainly at the middle level, causing the strength increase of southwest vortex (SWV), and acts as a connection between the positive vorticity centers at the upper and lower layers. For the microscopic cloud structure, the vertical updraft of the cloud cluster embedded in the SWV increases as the low-pressure system from the plateau arrives at the Sichuan Basin. Vapor and liquid cloud water at the lower level are transported upward, based on which the ice cloud at the upper level and the warm cloud at the lower level are joined to create favorable conditions for the growth of ice crystals. As the ice crystals grow up, snow and graupel particles form, which substantially elevates the precipitation. This effect leads to the rapid development of SWV rainstorm clouds and the occurrence of precipitation. In addition to the effect of the plateau vortex, the subsequent merging of the convective clouds is another important factor for heavy rainfall because it also leads to development of convective clouds, causing heavy rainfall.